PENGARUH PRE OPERATING TEACHING (INFORM CONSENT) TERHADAP PENURUNAN TINGKAT KECEMASAN PADA PASIEN PRE OPERATIF SECTIO CESARIA DI RUMAH SAKIT X DENPASAR - Iyut Putu Dessy Guritnawati; I Nyoman Sutresna; A.A Kompiang Ngurah Darmawan (Universitas Kusuma Husada Surakarta, 2021)
Inadequate health information can increase anxious reactions in patients and their families so that the preoperative information for cesarean section (informed consent) provided by officers aims to straighten out the patient's inaccurate perception or understanding of surgery. This study aims to see